1996
DOI: 10.1063/1.361161
|View full text |Cite
|
Sign up to set email alerts
|

Ion energy, ion flux, and ion mass effects on low-temperature silicon epitaxy using low-energy ion bombardment process

Abstract: In low-temperature (300–350 °C) silicon epitaxy employing low-energy inert-gas ion bombardment on a growing film surface, the effects of ion bombardment energy and ion flux as well as that of ion species on the crystallinity of a grown silicon film have been experimentally investigated. It is shown that the energy dose determined by the product of ion energy and ion flux is a main factor for epitaxy that compensates for the reduction in the substrate temperature. Large-mass, large-radius ion bombardment using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
32
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 13 publications
1
32
0
Order By: Relevance
“…One feature of IBAD that has been widely discussed is enhanced surface diffusion. Much of the evidence for this is indirect, e.g., reductions in minimum temperature for epitaxial growth [2] or changes in island size distributions during Volmer-Weber nucleation [1]. Recently, Ditchfield and Seebauer directly observed Ar ion-enhanced Ge surface transport on Si(111) using optical second harmonic microscopy [4].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One feature of IBAD that has been widely discussed is enhanced surface diffusion. Much of the evidence for this is indirect, e.g., reductions in minimum temperature for epitaxial growth [2] or changes in island size distributions during Volmer-Weber nucleation [1]. Recently, Ditchfield and Seebauer directly observed Ar ion-enhanced Ge surface transport on Si(111) using optical second harmonic microscopy [4].…”
mentioning
confidence: 99%
“…Ion beam assisted deposition (IBAD) is an important technique for modifying the structure and properties of thin film materials [1][2][3]. One feature of IBAD that has been widely discussed is enhanced surface diffusion.…”
mentioning
confidence: 99%
“…As shown in these spectra, a change in the additive gas changed the crystallization percentage and the use of an additive inert gas having a higher atomic mass improved the crystallinity of the deposited nc-Si:H film. It has been reported that Xe bombardment is more effective than Ar bombardment, which is generally used in PECVD, in enhancing the film quality [15,16]. This is related to the large mass of Xe as discussed previously in Fig.…”
Section: Resultsmentioning
confidence: 95%
“…Though target bias voltage is constant, the bombardment of higher doses of Ar ions enhances the ratio of ions per neutral atoms (I/A ratio) on the substrate. There have been many reports that deposited film properties such as resistivity, microstructure and texture were influenced by the increment of bombarding ion flux on the substrate [22][23][24][25]. Therefore, the increase of plasma density with reservoir temperature can improve the crystallinity of ITO films, which results in the lowest specific resistivity and the highest transmittance.…”
Section: Resultsmentioning
confidence: 98%